201k views
2 votes
Example: Solve the equation 5(x+1)−(6x−9)÷3=20+x−6

Solution: First simplify expressions on both sides of the equation:

Use distributive property to open parenthesis: 5x+5−(2x−3) = 20+x−6

5x+5−2x+3 = 20+x−6
Combine like terms: 3x+8 = 14+x
−x −x
2x+8 = 14
−8 −8
2x = 6
÷2 ÷2
x = 3

Answer: x=3
Answer:
Solve the equations :
Problem 1 : 5(2x − 14) = 5x + 15
Answer :

Problem 5 : 94 = 5(2m + 2) + 2m
Answer :

Problem 2 : 4(y + 5) − 3 = 6y − 13
Answer :

Problem 6 : 3 + 4(6 + 5n) = 3(7n + 6)
Answer :

Problem 3 : 7(t − 3) = 6(t − 2)
Answer :

Problem 7 : 8 + f = 5f − 5(f − 9)
Answer :

Problem 4 : y − 18 = 6(2 − 3y + 10) + y
Answer :
Problem 8 : 12 = 47k − 5(9k − 2)
Answer

User Eborrallo
by
4.5k points

2 Answers

1 vote

Answer:

X= 3

Explanation:

DUH

User Codutie
by
5.1k points
4 votes

Answer:

x= 3

Explanation:

User JJ Zabkar
by
5.2k points